Endoscopic Suturing for Defect Closure in the Upper Gastrointestinal Tract: A Retrospective Cohort Study - Apostolis Papaefthymiou; Nasar Aslam; Benjamin Norton; Andrea Telese; Charles Murray; Alberto Murino; Gavin Johnson; Roberto Simons-Linares; Rehan Haidry (Gastrointestinal Disorders)
Background: The increasing availability of gastrointestinal (GI) interventions has raised the need to treat luminal defects. Endoscopic suturing (ES) is a minimally invasive technique that is used for a wide range of indications. This retrospective cohort study aimed to evaluate the performance of ES in treating upper GI defects. Materials and Methods: Data from a tertiary centre were collected for patients undergoing ES to treat upper GI defects. The primary outcome was long-term outcomes, defined as the successful sutures deployment. Secondary outcomes included technical success, immediate clinical success (confirmation of closure at the time of the procedure), recurrence, and complications. Descriptive statistics and x2 test were used to calculate the rates of the outcomes and assess any link between independent variables and results. Results: Forty-two procedures were performed on 25 patients between 2018 and 2023. The mean age was 55 (±16.2) years, and 56% were female. The long-term clinical success rate was 69.6% (16/23), the technical success rate was 88.1% (37/42), and the immediate clinical success rate was 91.9% (34/37), with only two (4.8%) adverse events. The overall recurrence rate was 61.8% (21/34). Technical success was higher in the esophagus (92.3%), and stomach (100%) (p = 0.002), and immediate clinical success was more likely in patients with leaks (88.9%) or fistula (95.2%) compared to perforation (50%; p = 0.005). Conclusions: ES demonstrated high rates of technical and immediate clinical success for defect closure in the upper GI tract, with low rates of complications. The benefit is most prominently seen among patients with leaks and fistulas in the stomach and esophagus.